Geologic time scale 2020 - Gradstein, F. M.; Ogg, James G. (James George), 1952-; Schmitz, Mark D.; Ogg, Gabi (Elsevier, 2020)
Contains contributions from 80+ leading scientists who present syntheses in an easy-to-understand format that includes numerous color charts, maps and photographs. In addition to detailed overviews of chronostratigraphy, evolution, geochemistry, sequence stratigraphy and planetary geology, the GTS2020 volumes have separate chapters on each geologic period with compilations of the history of divisions, the current GSSPs (global boundary stratotypes), detailed bio-geochem-sequence correlation charts, and derivation of the age models. The authors are on the forefront of chronostratigraphic research and initiatives surrounding the creation of an international geologic time scale. The included charts display the most up-to-date, international standard as ratified by the International Commission on Stratigraphy and the International Union of Geological Sciences. As the framework for deciphering the history of our planet Earth, this book is essential for practicing Earth Scientists and academics. Key Features: Completely updated geologic time scale. Provides the most detailed integrated geologic time scale available that compiles and synthesize information in one reference. Gives insights on the construction, strengths and limitations of the geological time scale that greatly enhances its function and its utility.--Provided by publisher.